Psychological Structure and Physical Collapses in the Play (Tokous Alisharat Wa Altahawolat) by Saadalla Wan nous - Hamo , Horia; Hasan , Dania (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Saadalla Wannous had no embarrassment in expressing the individual tendencies and inclinations which he used to consider bourgeoisie matters. He started to feel with a kind of freedom , which he always believed in, which was the substantial condition for the realization of the Stage efficiency, and which he missed in his previous creativities. Previously, he used to impose on himself self-censorship which obliged him to overpass what is personal and individual. That is why we see him in his Play (Tokous Alisharat Wa Altahawolat) (Rites of Signs and Conversions) moves from the general condition to the individual structure within the context of the community. He strictly refers in this Play to the concept of the individual freedom through the psychological structure and subduing the will potential in the human self. Thus, he made his characters express their inner selves far from the social preaching, that lead towards their fate.